Transdisciplinarity: From Nicolescu's Postulates to Morin's Complex Thinking and their Repercussion in the Educational Setting - Zamora-Araya, José Andrey (2019)
This essay provides a reflection on the importance of complex thinking and transdisciplinarity in the educational context. For this, the contributions of Edgar Morin and Basarab Nicolescu are taken as references. In a first instance, relevant aspects of their proposals are presented such as the concepts of complexity, complex thinking, differences among the concepts of transdisciplinarity, interdisciplinarity and pluridisciplinarity, the levels of reality, and the logic of the included middle, exemplified by non-Euclidean geometries. In a second instance, the interrelation between the concepts of complexity and transdisciplinarity is shown, taking the work of Morin and Nicolescu as a base. In addition, the implications of transdisciplinary approaches and complex thinking in teaching-learning processes are explored in the educational context. Finally, we reflect on the need to move from simple to complex thinking and how transdisciplinarity can help to improve educational processes.